Do patients who die from an alcohol-related condition 'drift' into areas of greater deprivation? Alcohol-related mortality and health selection theory in Scotland. Issue 2 (7th December 2017) - Pulford, Andrew; Gordon, Ruth; Graham, Lesley; Lewsey, James; McCartney, Gerry; Robinson, Mark
Abstract : Background: Health selection has been proposed to explain the patterning of alcohol-related mortality by area deprivation. This study investigated whether persons who die from alcohol-related conditions are more likely to experience social drift than those who die from other causes. Methods: Deaths recorded in Scotland (2013, > 21 years) were coded as 'alcohol-related' or 'other' and by deprivation decile of residence at death. Acute hospital admissions data from 1996 to 2012 were used to provide premortality deprivation data. χ² tests estimated the difference between observed and expected alcohol-related deaths by first Scottish Index of Multiple Deprivation (SIMD) decile and type of death. Logistic regression models were fitted using type of death as the outcome of interest and change in SIMD decile as the exposure of interest. Results: Of 47 012 deaths, 1458 were alcohol-related. Upward and downward mobility was observed for both types of death. An estimated 31 more deaths than expected were classified 'alcohol-related' among cases whose deprivation score decreased, while 204 more deaths than expected were classified 'alcohol-related' among cases whose initial deprivation ranking was in the four most deprived deciles. Becoming more deprived and first deprivation category were both associated with increased odds of type of death being alcohol-related after adjusting for confounders. Conclusion: This study suggests that health selection appears to contribute less to the deprivation gradient in alcohol-related mortality in Scotland than an individual's initial area deprivation category.